Polypropylene–nano‐silica nanocomposite foams: mechanisms underlying foamability, and foam microstructure, crystallinity and mechanical properties. Issue 4 (23rd January 2020) - Kumar, Anish; Patham, Bhaskar; Mohanty, Smita; Nayak, Sanjay Kumar
Abstract: We investigate the production and characterization of foams prepared from polypropylene (PP) as well as PP–silica nanocomposites containing different loadings of nano‐silica. This study was carried out to investigate the mechanisms underlying the production of foams with a regular cell structure through the use of nano‐scale fillers. Foaming was carried out in batch mode using an autoclave with CO2 as the physical blowing agent; high pressures of the order of 14 MPa were achieved through a combination of active pressurization and the use of high foaming temperatures. The resulting PP nanocomposite foams were characterized in detail to quantify the effect of the nano‐silica loading on the foam density and mechanical, morphological and thermal properties. The addition of nano‐silica in PP resulted in the improvement of foam quality – as assessed from the well‐defined and regular cell structures with absence of cell coalescence – as well as an increase in expansion ratio and decrease in foam density. Careful analyses of trends in cell size, cell density and expansion ratio of the foams were correlated with measurements of melt rheology and nano‐filler morphology of the unfoamed specimens in order to identify subtle details regarding the role of silica nanoparticles in improving foam quality. © 2019 Society of Chemical Industry Abstract :